The Glycoprotease CpaA Secreted by Medically Relevant Acinetobacter Species Targets Multiple O-Linked Host Glycoproteins - M. Florencia Haurat (American Society for Microbiology, 2020)
ABSTRACT Glycans decorate proteins and affect their biological function, including protection against proteolytic degradation. However, pathogenic, and commensal bacteria have evolved specific glycoproteases that overcome the steric impediment posed by carbohydrates, cleaving glycoproteins precisely at their glycosylation site(s). Medically relevant Acinetobacter strains employ their type II secretion system (T2SS) to secrete the glycoprotease CpaA, which contributes to virulence. Previously, CpaA was shown to cleave two O-linked glycoproteins, factors V and XII, leading to reduced blood coagulation. In this work, we show that CpaA cleaves a broader range of O-linked human glycoproteins, including several glycoproteins involved in complement activation, such as CD55 and CD46. However, only CD55 was removed from the cell surface, while CD46 remained unaltered during the Acinetobacter nosocomialis infection assay. We show that CpaA has a unique consensus target sequence that consists of a glycosylated serine or threonine residue after a proline residue (P-S/T), and its activity is not affected by sialic acids. Molecular modeling and mutagenesis analysis of CpaA suggest that the indole ring of Trp493 and the ring of the Pro residue in the substrate form a key interaction that contributes to CpaA sequence selectivity. Similar bacterial glycoproteases have recently gained attention as tools for proteomic analysis of human glycoproteins, and CpaA appears to be a robust and attractive new component of the glycoproteomics toolbox. Combined, our work provides insight into the function and possible application of CpaA, a member of a widespread class of broad-spectrum bacterial glycoproteases involved in host-pathogen interactions. IMPORTANCE CpaA is a glycoprotease expressed by members of the Acinetobacter baumannii-calcoaceticus complex, and it is the first bona fide secreted virulence factor identified in these species. Here, we show that CpaA cleaves multiple targets precisely at O-glycosylation sites preceded by a Pro residue. This feature, together with the observation that sialic acid does not impact CpaA activity, makes this enzyme an attractive tool for the analysis of O-linked human protein for biotechnical and diagnostic purposes. Previous work identified proteins involved in blood coagulation as targets of CpaA. Our work broadens the set of targets of CpaA, pointing toward additional roles in bacterium-host interactions. We propose that CpaA belongs to an expanding class of functionally defined glycoproteases that targets multiple O-linked host glycoproteins.